نموذج مقترح للتميز المؤسسي في المستشفيات : دراسة ميدانية على المستشفيات الحكومية المصرية الواقعة في القاهرة الكبرى - بركات، محمد علي (جامعة الملك سعود, 2019)
تتمثل مشكلة البحث في عدم الإدراك الكافي لبعض مديري المستشفيات المصرية الحكومية للعوامل الحاكمة والمؤثرة على الأداء المتميز لتلك المستشفيات. والهدف الرئيسي لهذه الدراسة هو بناء واختبار نموذج للتميز المؤسسي في المستشفيات المصرية. وقد واستخدم الباحث المنهج الاستقرائي لوضع فروض البحث، والمنهج الاستنباطي لاختبار صحة فروض البحث. بلغت عينة البحث ٤٠٠ مدير مستشفى، وبلغ عدد الاستمارات الصالحة للتحليل ٣٢٢ استمارة، وبلغ معدل الاستجابة للاستقصاء الموجه لمديري المستشفيات موضع الدراسة 80.5%. لقد استخدم الباحث اختبار الاعتمادية باستخدام معامل ألفا كرونباخ لاختبار ثبات واعتمادية المقاييس المستخدمة في الدراسة، كما استخدم التحليل العاملي التأكيدي لاختبار صدق وصلاحية المقاييس المستخدمة في الدراسة، كما استخدم تحليل المسار لاختبار صلاحية النموذج المجمع النهائي ككل. واستخدم الباحث أيضا تحليل الارتباط والانحدار لاختبار معنوية العلاقات بين عوامل الدراسة. وقد توصل الباحث إلى عدة نتائج هي أنه توجد علاقة معنوية وإيجابية بين إدارة المعرفة والتركيز على المرضي، وبين إدارة الأنشطة في المستشفى، وأن هناك علاقة معنوية وإيجابية بين القيادة وإدارة الأنشطة، وبين نتائج الأداء الكلي للمستشفى.
Research problem can be represented as follows: Some managers of Egyptian Hospitals do not perceive adequately the critical factors that may affect the excellent performance of these hospitals. The main aim of this study is to build and test a model for business excellence in Egyptian hospitals. The researcher used inductive approach to set research hypotheses and the researcher used deductive approach to test research hypotheses. Sample size was 400 managers. The number of Valid questionnaires was 322 .The rate of response was 80.5%. The researcher used reliability test using Alpha Cronbach coefficient to test reliability of scales of the study. The researcher also used confirmatory factor analysis to test the validity of scales of the study. The researcher used too path analysis to test the validity of the final model as whole. The researcher used also correlation and regression analysis to test the significance of relationships among the factors of research. The results of research indicated that there is a significant and positive relationship between Knowledge management, focus on patients and managing activities in hospitals. The results of research revealed also that there is a significant and positive relationship between leadership, managing activities, and overall performance results of hospital.
Keywords: المستشفيات الحكومية المصرية -- محافظة القاهرة -- الموارد البشرية -- التنمية البشرية -- الوقاية والعلاج -- الأمراض -- مصر -- المجتمع المصري